The association of the COVID-19 outbreak with in-hospital mortality: A single-centre study from Indonesia - Hadiki Habib; Yogi Prabowo; Septo Sulistio; Radi Muharris Mulyana; Imamul Aziz Albar (Elsevier, 2023)
Objective: The early outbreak period of Coronavirus Disease (COVID-19) has affected the emergency department (ED) and hospital services in many countries. This study aimed to investigate the association between COVID-19 outbreak and in-hospital mortality in Jakarta, Indonesia. Methods: This retrospective cohort study was conducted in a single-centre referral hospital in Jakarta, Indonesia. Data were collected between May and October 2020. All patients who visited the ED and required inpatient care during the early COVID-19 outbreak period at the study location (March to April 2020) were included in the exposure group. All patients who visited the ED and required inpatient care during the non-outbreak period (March to April 2019) were included in the non-exposure group. In-hospital mortality was the primary outcome, whereas other variables, such as sex, age, triage categories, trauma cases, referral cases, and ED length of stay (LOS), were measured to identify confounding and effect modifications. Multivariate logistic regression analysis was performed to assess this association. Results: A total of 2,808 patients during the outbreak period and 2,423 patients during the non-outbreak period participated in the study. The odds of in-hospital mortality increased during the outbreak period compared to that during the non-outbreak period (odds ratio [OR], 1.41; 95%CI 1.04-1.91; p = 0.01) after adjusting for age, sex, triage categories, trauma case, ED LOS, and interaction between the outbreak period and ED LOS. Conclusion: COVID-19 outbreaks have been associated with an increased risk of in-hospital mortality in referral hospitals in Jakarta, Indonesia.